Twenty four-hour urine collection is appropriate in a cohort of South African renal stone formers - Kaestner, Lisa; Lazarus, John; Muller, Elmi (African Journal of Nephrology, 2021)
Objectives: To report the prevalence of metabolic abnormalities found in an urban South African population of stone formers and thereby determine whether international guidelines on 24-hour urine collection should be recommended for South African stone formers. Methods: A retrospective folder review was conducted on patients who were admitted with renal stones or who had renal stone procedures between 1 November 2014 and 31 March 2020, with a confirmed history of renal calculi and who had 24-hour urine collection at a tertiary centre renal stone clinic. All confirmed stone formers were offered 24-hour urine collection once they were infection-free and stone-free. Demographics, 24-hour urine collection findings and stone analysis results (if available) were recorded. A 24-hour urine collection was performed once patients were stone-free while on their regular diet and routine lifestyle. Results: 175 patients with metabolic studies were included (65 females and 110 males). The mean age was 53.8 ±13.6 years. The commonest metabolic risk factors were hypocitraturia (61.0%), hypomagnesiuria (41.1%), mild hypercalciuria (22.0%), and hyperuricosuria (20.2%). Hyperuricaemia, high urinary sodium excretion, mild hypercalciuria and hyperuricosuria were more common in men. A total of 102 patients had both 24-hour urine collection and stone analysis for comparison. There were no differences between different stone types in the prevalence of metabolic risk factors except for hyperuricaemia and high urinary sodium excretion, which were both higher in uric acid predominant stone formers. Conclusion: The prevalence of risk factors was high and seemed similar to that of other populations, except for a higher prevalence of hypocitraturia. Internationally recommended guidelines for 24-hour urine studies are therefore applicable and appropriate for this population. Risk factors seem similar across stone types; however, a larger study is necessary to clarify whether metabolic risk factors are useful to predict stone composition.